A Miniaturized 878 MHz Slotted Meander Line Monopole Antenna - Nabilah Ripin; Ahmad Asari Sulaiman; Nur Emileen Abd Rashid; Mohamad Fahmi Hussin; Nor Najwa Ismail (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
A slotted meander line printed monopole antenna for low frequency applications at 878 MHz is presented. The operating frequency of the conventional printed monopole antenna was greatly reduced by the presence of the slots and meander line which lead to the reduction of the antenna size. The size reduction up to 70% compared to the conventional reference antenna is achieved in this study. The antenna has a simple structure and small antenna size of 46.8 mm x 74 mm or 0.137????0 x 0.217????0. The antenna has been fabricated on the low-cost FR4 substrate and measured to validate the simulation performances. Measured results display that the proposed antenna produces omnidirectional radiation pattern of impedance bandwidth of 48.83 MHz and the maximum gain of -1.18 dBi.